Territórios de escuta e imagens em movimento: um (discreto) deslocamento epistemológico - Frederico Augusto Vianna de Assis Pessoa (2017)
In this research, we investigate what we call Listening Territories - listening spaces that bring together different experiences, personal/cultural history and sensibility connected to sound.Listening reflects not only a locatable point of sensory reception, but a confluence that combine our experiences of the world, the diverse interpretations we give to what we hear, as well as the devices that modulate our perceptions - our geographic-cultural location, ourhistory social and personal, our relationship with technology, as well as the different systems of thought that we build from listening. We discuss listening as form of knowledge about the world, surpassing its sensorial aspect and embracing the symbolic field that it constitutes in our experiences. Then, we approach the Listening Territories in the cinema, analyzing how these territories are central in the constitution of the cinematographic experience. A film proposes a way of thinking, organizing, composing, articulating and valuing sounds - but, ourhypothesis, is that a film can only accomplish it in the interaction with the listener/viewer. Listening territories in cinema involve all thinking and experience with sounds that precedes them: daily experiences with sound as well as experiences with sound through other artisticworks. In this sense, we are interested in understanding how cinema articulates, creates and presents those sound spaces, but also how the subjective interaction of the spectator with this universe of meanings occurs. Our hypothesis is that listening has a cultural and personalhistory (anthropological and subjective) and that it constitutes such territories. If, on one hand, we find rigid functions for the sounds within the cinematic industry that end up limiting the emergence of these territories, leading to a standardization of both - the poetic constructions and the reception of the spectators. On the other, we observe forms of soundexperimentation that proposes listening territories of resistance, far from the standards established by the industries. Our hypotheses is that these territories of resistance are influenced by the sound-musical researches of rupture that occurred during the XX century, which altered our daily sound perception of the world and, as a consequence, altered ourunderstanding of this world, and allowed a wide opening for the experimentation in the arts that use sound as a compositional element.